2022
DOI: 10.1093/plphys/kiac451
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis plastid carbonic anhydrase βCA5 is important for normal plant growth

Abstract: Carbonic anhydrases (CAs) are zinc-metalloenzymes that catalyze the interconversion of CO2 and HCO3-. In heterotrophic organisms, CAs provide HCO3- for metabolic pathways requiring a carboxylation step. Arabidopsis (Arabidopsis thaliana) has 14 α- and β-type CAs, two of which are plastid CAs designated as βCA1 and βCA5. To study their physiological properties, we obtained knock-out (KO) lines for βCA1 (SALK_106570) and βCA5 (SALK_121932). These mutant lines were confirmed by genomic PCR, RT-PCR, and immunoblot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Both MGDGs and DGDGs are involved in many aspects of photosynthesis and chloroplast integrity [(for review, see Li and Yu, 2018)]. Like βCA1, βCA5 supplies HCO 3 − , which is required for anaplerotic pathways in plastids, such as fatty acid biosynthesis (Weerasooriya et al., 2022). Moreover, similar to βca5 , an MGDG‐deficient mgd1 mutant displays reduced chlorophyll content and qN (NPQ), and no change in maximal PSII efficiency (Fv/Fm) compared with WT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both MGDGs and DGDGs are involved in many aspects of photosynthesis and chloroplast integrity [(for review, see Li and Yu, 2018)]. Like βCA1, βCA5 supplies HCO 3 − , which is required for anaplerotic pathways in plastids, such as fatty acid biosynthesis (Weerasooriya et al., 2022). Moreover, similar to βca5 , an MGDG‐deficient mgd1 mutant displays reduced chlorophyll content and qN (NPQ), and no change in maximal PSII efficiency (Fv/Fm) compared with WT.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study on the tissue expression of βCAs showed that βCA 1, βCA 2 and βCA 4 are mainly expressed in the aboveground tissues with almost no expression in roots, whereas βCA3 , βCA5 and βCA6 are expressed in all parts of the plant but at a lower level in roots (Fabre et al., 2007; Weerasooriya et al., 2022). Furthermore, it was found that βCA5 is expressed at much lower levels than βCA1 , and that the expression of βCA5 and βCA1 is sensitive to CO 2 concentrations (Wang et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To date, two separate plant lines have been generated wherein native CAs have been eliminated. Hines et al (2021) utilised CRISPR-Cas9 to knock out two tobacco stromal CAs (β-CA1 and β-CA5), while Weerasooriya et al (2022) used T-DNA insertion lines with inactivated plastid β-CA1 and β-CA5 in Arabidopsis thaliana. The stunted growth and reduced pollen fertility phenotypes of these plants, in particular of β-ca1/β-ca5, demonstrated that plastid CAs play an essential metabolic role in supplying bicarbonate for anaplerotic reactions (Hines et al, 2021;Weerasooriya et al, 2022).…”
Section: Carbonic Anhydrasementioning
confidence: 99%
“…In Arabidopsis, γ-type CAs are usually located in mitochondria as important subunits of mitochondrial complex I and are required for normal embryogenesis and photomorphogenesis [ 31 , 32 , 33 ]. β-type CAs have been demonstrated to be important to maintaining stomatal development and function as well as plant growth and responses to various stresses [ 34 , 35 , 36 , 37 , 38 ]. Although it has been suggested that AtαCA2, AtαCA4, and AtαCA5 are involved in photosynthetic light reactions, their corresponding functions and underlying mechanisms remain to be deciphered [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%